Hypothyroidism in Children with Β-Thalassemia at a Tertiary Hospital of South Punjab, Pakistan - Tayyaba Batool, Shomaila Irim, Malik Muhammad Naeem, Badar Mehmood, Nadeem Shahid Younas, Muhammad Irfan Khan, Khadija Nadeem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of hypothyroidism among children with β-thalassemia major. Study Design: Cross-sectional study. Place and Duration of the Study: The Department of Hematological Disorder, Thalassemia and Bone Marrow Transplantation Centre, and Department of Biochemistry, Bahawal-Victoria Hospital, Quaid e Azam Medical College”, Bahawalpur, Pakistan from 1st January 2021 to 31st December 2021. Methodology: A total of 125 children of both genders (2 to 18 years) with diagnosis of β-thalassemia major were analyzed. Two ml blood sample under strict aseptic conditions was obtained from every study participant and sent to Institutional Pathological Laboratory for thyroid-stimulating hormone (TSH), T3, and T4. Results: In a total of 125 children with β-thalassemia major, 78 (62.4%) were male. Overall, mean age was 8.57±4.75 years while 57 (45.6%) children were aged between 6 to 10 years. Residential status of 84 (67.2%) children was rural. Parental consanguineous marriages were reported in 91 (72.8%) patients. Mean TSH, T3 and T4 levels were calculated to be 3.27±1.38 pmol/L, 4.71±0.75 pmol/L and 11.80±2.38 pmol/L respectively. Hypothyroidism was noticed in 38 (30.4%) children. Conclusion: Prevalence of hypothyroidism in children with β-thalassemia major was high. Early identification and management of hypothyroidism in β-thalassemia major may improve overall quality of life among these affected children Keywords: Β-thalassemia major, hypothyroidism, thyroid-stimulating hormone.